Two isomeric Cd-viologen coordination polymers with photochromic and photoluminescence properties. (January 2021) - Li, Xiao-Nan; Li, Li; Wang, Zhi-Hui; Wu, Gui-Hong; Liu, Si-Qi; Zhang, Hong
Abstract: Two novel isomeric Cd-viologen coordination polymers [Cd(CV)0.5 ·( p -BDC)·H2 O] (1 ) and [Cd(CV)0.5 ·( m -BDC)·H2 O] (2 ) (CV= N, N′ -4, 4′-bipyridiniodipropionate, p -BDC 2−  = terephthalate, m -BDC 2−  = isophthalate) have been successfully assembled and well characterized. Compounds 1 and 2 have the same empirical formula but different structures. Isomer 1 exhibits a 3D structure, while compound 2 exhibits a 1D channel structure. Interestingly, the photochromic behaviors of the two compounds were different due to different electron transfer pathways, with compound 1 reaching light saturation at 80 min and compound 2 reaching light saturation at 35 min. Furthermore, we also studied the photofluorescence of two isomers to enrich the crystal properties. Graphical abstract: Image 1 Highlights: Two novel Cd-viologen isomers with photochromic and photoluminescence properties were synthesized. Two isomeric coordination polymers exhibit different structures and photochromic properties. The electron transfer pathways determine the difference of photochromic properties of two isomers.